Serum neurofilament levels in patients with multiple sclerosis: A comparison of SIMOA and high sensitivity ELISA assays and contributing factors to ELISA levels - Revendova, K Zondra; Zeman, D; Bunganic, R; Karasova, K; Volny, O; Bar, M; Kusnierova, P (Multiple sclerosis and related disorders, 2022)
BACKGROUND: Serum neurofilaments (sNfs), especially the most investigated serum neurofilament light chain (sNfL), are promising biomarkers in multiple sclerosis (MS). However, their clinical utility is still limited, given the availability and costs of accessible analytical methods. The gold standard for the detection of sNfs is represented by the single molecule arrays (SIMOA). Recently, a high sensitivity enzyme-linked immunosorbent assay (hsELISA) has also been introduced. The objective of the study was to compare both assays for the determination of sNfL and neurofilament heavy chain (sNfH) concentrations in a defined MS cohort. The second objective was to identify contributing factors to sNfs concentrations determined by hsELISA. METHODS: Serum samples were collected from MS patients attending the MS Centre, University Hospital Ostrava, Czech Republic. The levels of sNfs were detected using SIMOA and hsELISA assays. RESULTS: The Spearman's rank correlation coefficient between the sNfL SIMOA and sNfL hsELISA and between the sNfH SIMOA and sNfH hsELISA was moderate rs= 0.543 (p = 0.001) and rs= 0.583 (p = 0.001), respectively. The Passing-Bablok regression analysis demonstrated bias between both methods. Equally significant bias between the methods was confirmed by the Bland-Altman plots. Furthermore, confounding factors affecting the sNfL levels were glomerular filtration rate (eGFR; 95% CI -2.34 to -0.04) and sex (95% CI -2.38 to -0.10). The sNfH levels were affected by age (95% CI 0.01 to 0.07), eGFR (95% CI -2.45 to -0.02), body mass index (BMI; 95% CI -0.31 to -0.05), and blood volume (95% CI 0.69 to 3.35). CONCLUSION: This analytical study showed significant differences between hsELISA and SIMOA methods, especially for the sNfH concentrations. We identified confounding factors for sNfs levels determined by hsELISA. The sNfs levels were influenced by renal function and sex, whilst sNfH levels were affected by age, BMI, and total blood volume.
Keywords: Česká republika; Intermediate Filaments; Enzyme-Linked Immunosorbent Assay; intermediární filamenta; lidé; Multiple Sclerosis; High sensitivity ELISA; ELISA; Multiple sclerosis; Neurofilament heavy chain; SIMOA; biologické markery; Czech Republic; roztroušená skleróza; Biomarkers; Neurofilament light chain; Humans